REVIEW OF MUAMALAH FIQH IN THE PRACTICE OF DURIAN PLANTATION LAND MANAGEMENT USING THE PARON SYSTEM - Khusnia, Chinta; Asnawi, Nur; Meldona (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Based on the review of the fiqh of muamalah Ibn Taymiyah (Qardawi, No. 328) regarding the development of plantation land management, the most appropriate contract to be used is the Musaqah contract scheme. However, there is often a discrepancy between agricultural theory and practice that occurs in the field, both in terms of profit sharing, the application of contracts, and even other reviews of muamalah fiqh. The many problems that arise in the implementation of the profit-sharing system and the sale and purchase of durian fruits that are still on the tree cause unhappiness in one of the parties who perform the contract. This study uses a qualitative method with a case study approach. The goal is to focus on the review of muamalah fiqh on the paron (profit sharing) system and the durian fruit buying and selling system that is still on the tree. The results of the study show that the durian tree plantation paron system in Sumberrejo Village, Purwosari District, Pasuruan Regency is carried out only based on trust and honesty because they already know each other. However, because the cooperation agreement is not written or oral, the terms and conditions of the contract can be concluded not following Islamic sharia (fiqh muamalah). Likewise, the review of fiqh muamalah on the system of buying and selling durian fruits that are still on the tree, this system is not allowed, because the profit is not known.